Adulteration of the Herbal Weight Loss Products by the Illegal Addition of Synthetic Antiobesity Medications: A Pilot Study - Farzin Firozian; Amir Nili-Ahmadabadi; Shirin Moradkhani; Miad Moulaei; Zohreh Fasihi; Davoud Ahmadimoghaddam (Hindawi Limited, 2021)
Background. Some anorexic agents are used to fraudulent augmentation herbal weight loss formulations. This study was designed to evaluate the potential existence of illicit substances in 63 herbal weight loss formulations collected from local apothecaries in Hamadan, Iran. Methods. The thin-layer chromatography method was applied for the primary screening of potential illicit substances in the samples. The positive samples were analyzed using an isocratic high-performance liquid chromatography method. Results. The results showed that 26.98% of the samples contained 17.76 ± 6.02 mg/cap of sibutramine. Daily therapeutic dose intake of sibutramine is in the range of 5 to 15 mg daily. Conclusion. Since apothecaries have advised consumers to take at least two capsules a day, it seems that the blood concentration of sibutramine will likely rise beyond the therapeutic concentration and become toxic. Therefore, the usage of such products could pose serious risks to consumers' health.